Sedimentary and geomorphic evidence of Saharan megalakes: A synthesis. (15th January 2022) - Drake, N.A.; Candy, I.; Breeze, P.; Armitage, S.J.; Gasmi, N.; Schwenninger, J.L.; Peat, D.; Manning, K.
Abstract: It has long been recognised that the Sahara Desert contains sediment, landform and palaeoecological evidence for phases of increased humidity during the Quaternary period. Many authors have also suggested that during some of these humid periods very large lakes, termed megalakes, developed in several basins within the Sahara. Recent work has questioned their existence. In particular it has been argued that the lack of well-developed and spatially extensive shorelines in these basins suggests that discrete groundwater and spring deposits have been misinterpreted as evidence for megalakes. In this paper we re-evaluate the evidence used to identify megalakes. Firstly, we apply a comprehensive remote sensing and GIS analyses to the megalake shorelines, their catchments and the wider Sahara. This not only supports the previously proposed existence of numerous megalakes, but also indicates a previously unrecognised megalake in the Niger Inland Delta region, here named Megalake Timbuktu. Secondly, we review the geomorphic and sedimentary evidence for the megalakes, highlighting the importance of the sedimentary record in identifying lake highstands, particularly through the example of the Chotts Megalake in southern Tunisia where we provide new sedimentary information on lake shorelines. This analysis demonstrates that in much of the Sahara the dynamic aeolian systems preclude the preservation of well-developed shorelines, but the distribution of fragmented geomorphic features and localised lake deposits provide robust evidence for Quaternary megalake formation. The paper concludes by highlighting that although extensive evidence for Saharan megalake formation exists, the current chronology of lake highstands indicates that the vast majority date to Marine Isotope Stage (MIS) 5 or earlier. Only megalakes Chad and Timbuktu, which derive much of their water from outside the desert, show evidence for Holocene (African Humid Period or AHP) shorelines. The AHP record of the other megalakes indicate the existence of much smaller water bodies than those that developed earlier in the Pleistocene indicating that it was significantly drier than these earlier humid phases. Highlights: Many studies have reported evidence for megalakes in the Sahara, yet recent work has questioned their existence. A comprehensive remote sensing analyses of the entire Sahara supports the presence of most previously proposed megalakes, This analysis reveals a new megalake that we call Megalake Timbuktu. A review of the evidence for megalakes highlights the importance of the sedimentary record in their identification. The chronology of lake highstands indicates that the vast majority date to Marine Isotope Stage (MIS) 5 or earlier.